2015
DOI: 10.5070/d3213022834
|View full text |Cite
|
Sign up to set email alerts
|

Lipoid Proteinosis: a case report in two siblings

Abstract: Lipoid proteinosis was first reported by Urbach and Wiethe in 1929. It is also known as hyalinosis cutis et mucosae or Urbach-Wiethe disease. It is a rare autosomal recessive disorder and characterized by the infiltration of hyaline material in the skin, oral cavity, larynx, and internal organs. Lipid proteinosis presents early in life. Hoarseness develops in infancy. The classic sign is beaded eyelid papules along the lid margin, also known as 'Monilform Blepherosis'. In India about 30 cases have been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Hence, review of 51 cases of LP reported in India from 1969 to 2021 is done along with the present case [ Table 1a – c ]. [ 1 4 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] LP is more reported in patients in the age group of 11-20 (51%). More prevalence of LP is reported in males (70.6%).…”
Section: Review and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, review of 51 cases of LP reported in India from 1969 to 2021 is done along with the present case [ Table 1a – c ]. [ 1 4 5 6 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] LP is more reported in patients in the age group of 11-20 (51%). More prevalence of LP is reported in males (70.6%).…”
Section: Review and Discussionmentioning
confidence: 99%
“…On review of oral manifestations, 42 cases were found as shown in Table 1c . [ 1 4 5 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 25 26 27 28 29 30 31 32 33 34 35 37 38 39 42 43 44 ] The most common involved site is tongue with typical thick woody appearance followed by restricted tongue movements. In the present case, also similar findings were present.…”
Section: Review and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipoid proteinosis (Urbach-Weithe disease) is an autosomal recessive deposition disorder that occurs due to loss of function mutation of ECM1 on chromosome 1q21 which encodes extracellular matrix protein 1. [ 2 ] It is characterized by a weak cry at birth, hoarseness of voice, blistering that resolves with pock-like scarring, diffusely thickened waxy yellow skin, and enlarged tongue. [ 3 4 ] The classical clinical feature is beaded papules linearly arranged over the eyelid margin (Moniliform blepharosis).…”
mentioning
confidence: 99%